Contribuições do design thinking no ensino fundamental: anos iniciais em um contexto de aprendizagem por projeto - Licosa, Graziella Matarazzo di (2021)
This dissertation is part of the line of research New Technologies in Education, of the Graduate Program in Education: Curriculum of the Pontifical Catholic University of São Paulo. The study aimed to reflect on the application of the Design Thinking (DT) approach in Lower School, in a context of Project Based Learning. The specific objectives were to compile and systematize the fundamentals of the curricular proposal of the School in question in this research; narrate the journey of students of the 5th grade of a class from a private school in São Paulo with the DT approach; and to outline the possible dialogue between the curriculum and the journey analyzed, looking for identities and prominences. This proposition was based on an experimental field research, in which the researcher was also the protagonist of the process of teaching and learning through projects using the Design Thinking approach and became relevant because, even though all objects created since the emergence of humanity have passed through a design process, Design as a profession or scientific field is something recently defined. The methodology used was the research of qualitative and narrative approach, so that practices carried out in a private school in the city of São Paulo (SP) were counted. The main references of this work were Brown (2008, 2009, 2010), Moran (2017, 2018) Silva (1999), Goodlad (1977) and Abramowicz et al. (2006). In addition to the analysis of the pedagogical approach, this investigation seeks to identify the school's living curriculum that it imposes, according to what is proposed by John Inkster Goodlad (1977), surveying the experienced, the operational, the perceived and the formal curriculum. Furthermore, as participatory research, it seeks the progressive construction of knowledge that can be shared, starting from the critical theory of education and from the discussion on the role of active methodologies in the teaching and learning process in the 21st century. The research results suggest that the Design Thinking approach brings strategies that support the context of Project Based Learning, emphasizing, however, that it is necessary to pay attention to its effectiveness when part of a project, as it contains methodology with particularities that demand from the educator and the school's design of a curriculum that meets the specifics of this context